2019
DOI: 10.1080/02699206.2019.1604806
|View full text |Cite
|
Sign up to set email alerts
|

Rating the intelligibility of dysarthic speech amongst people with Parkinson’s Disease: a comparison of trained and untrained listeners

Abstract: Rating the intelligibility of dysarthic speech amongst people with Parkinson's Disease: a comparison of trained (Speech and Language Therapy students) and untrained listeners

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
0
6
1
Order By: Relevance
“…In terms of listener experience, the findings of this study support those of DePaul and Kent (2000) and McGarr (1983) in that the experienced group showed higher intelligibility scores compared with those of the naïve group. On the other hand, findings are in contrast to those in studies such as Smith et al (2019), who found no difference in scores obtained by orthographic transcription from trained and untrained listeners. However, the trained listeners in Smith et al's study were second year SLT students who might not have the same level of experience with unclear speech as the experienced listeners in the current study, who had been working with people with speech and learning difficulties for at least 3 years.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In terms of listener experience, the findings of this study support those of DePaul and Kent (2000) and McGarr (1983) in that the experienced group showed higher intelligibility scores compared with those of the naïve group. On the other hand, findings are in contrast to those in studies such as Smith et al (2019), who found no difference in scores obtained by orthographic transcription from trained and untrained listeners. However, the trained listeners in Smith et al's study were second year SLT students who might not have the same level of experience with unclear speech as the experienced listeners in the current study, who had been working with people with speech and learning difficulties for at least 3 years.…”
Section: Discussioncontrasting
confidence: 99%
“…McGarr (1983) suggested that the experienced listeners, who had at least a year's experience of listening to the speech of people who are deaf, were familiar with the speech characteristics of this group and were able to compensate for the atypical features. On the other hand, Smith et al (2019) also used orthographic transcription of sentences to compare intelligibility scores in speakers with PD when measured by experienced (SLT students) and inexperienced listeners, and found no difference between the two listener groups. It may be that if the listeners had more clinical experience, outcomes may have been different.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also anticipate that the new, individualized modeling approach of spectral brain pathology for each patient may translate and be meaningful to other clinical populations. Our approach to speech impairment quantification is predicated on the notion that clinical endpoints for speech production studies in PD need to improve speech perception by human raters [11][12][13]52,53 . One novel contribution of the present study is rating of speech features from non-experts through an intuitive and interactive app (Audio-Tokens) 54 , that facilitates simultaneous comparison of speech samples from multiple study participants.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal outcome of remediation speech therapies in PD is improved intelligibility to human listeners, hence the value of human assessment of speech impairments as an alternative. Human ratings of speech impairments in PD are highly reliable across raters [11][12][13] , time points 14 , and levels of rater expertise 13 , and can contribute to predicting disease progression 12 and therapeutic outcomes 14 beyond simpler acoustical metrics.…”
mentioning
confidence: 99%